Milestones in understanding transport, sensing, and signaling of the plant nutrient phosphorus - Yang, Shu-Yi; Lin, Wei-Yi; Hsiao, Yi-Min; Chiou, Tzyy-Jen (The Plant cell, 2024)
Abstract As an essential nutrient element, phosphorus (P) is primarily acquired and translocated as inorganic phosphate (Pi) by plant roots. Pi is often sequestered in the soil and becomes limited for plant growth. Plants have developed a sophisticated array of adaptive responses, termed P starvation responses, to cope with P deficiency by improving its external acquisition and internal utilization. Over the past 2 to 3 decades, remarkable progress has been made toward understanding how plants sense and respond to changing environmental P. This review provides an overview of the molecular mechanisms that regulate or coordinate P starvation responses, emphasizing P transport, sensing, and signaling. We present the major players and regulators responsible for Pi uptake and translocation. We then introduce how P is perceived at the root tip, how systemic P signaling is operated, and the mechanisms by which the intracellular P status is sensed and conveyed. Additionally, the recent exciting findings about the influence of P on plant-microbe interactions are highlighted. Finally, the challenges and prospects concerning the interplay between P and other nutrients and strategies to enhance P utilization efficiency are discussed. Insights obtained from this knowledge may guide future research endeavors in sustainable agriculture. This article reviews the molecular mechanisms of phosphorus transport, sensing and signaling; and highlights recent findings about the impact of phosphorus on plant-microbe interactions.